2018
DOI: 10.3168/jds.2017-14261
|View full text |Cite
|
Sign up to set email alerts
|

Use of β-glucan from spent brewer's yeast as a thickener in skimmed yogurt: Physicochemical, textural, and structural properties related to sensory perception

Abstract: Powdered β-glucan extracted from brewer's yeast (Yestimun, Leiber GmbH, Bramsche, Germany) was incorporated into skimmed-milk yogurt at varying concentrations (0.2-0.8% wt/wt) to investigate its potential application as a thickener. The effect of β-glucan fortification on the nutritional profile, microstructure, physicochemical properties, and texture of freshly prepared yogurts was investigated. Sensory evaluation was also conducted and was correlated with instrumental analysis. The addition of Yestimun signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…According to Table , the rest of the groups are the same caused varying levels of lactic acid bacteria. This finding has important economic implications for the yoghurt industry – reduced fermentation times can accelerate processing (Raikos et al ). Further studies are required to prove the effect of PE on the viability of lactic acid bacteria species, particularly the LCR, LAP and LP used in this study.…”
Section: Resultsmentioning
confidence: 98%
“…According to Table , the rest of the groups are the same caused varying levels of lactic acid bacteria. This finding has important economic implications for the yoghurt industry – reduced fermentation times can accelerate processing (Raikos et al ). Further studies are required to prove the effect of PE on the viability of lactic acid bacteria species, particularly the LCR, LAP and LP used in this study.…”
Section: Resultsmentioning
confidence: 98%
“…bulgaricus were used as yogurt cultures (Pappa et al, 2018). When incorporating powdered brewer's yeast β-glucans into yogurt at concentrations (0.2-0.8% wt/wt), the titratable acidity remained unaffected, textural properties showed a gradual increment of hardness, adhesive force, and cohesiveness with increasing β-glucan concentration (Raikos et al, 2018). In comparison with the non-fat yogurt without β-glucan (Mejri et al, 2014), the application of yeast β-glucan in yogurt improved the rheological properties and the physical stability of the product.…”
Section: Resultsmentioning
confidence: 99%
“…Also, when giving additional functional properties to the products, it is important at least to preserve the initial physicochemical, rheological and sensory properties. Many studies have shown the possibility of using β-glucans from different sources as thickeners, texturizers and even fat replacers (Khorshidian et al, 2018;Raikos et al, 2018). Hozova et al (2004) established that the addition of pleuran (glucan isolated from P. ostreatus) hydrogel to yogurt did not inhibit the fermentation ability of yoghurt cultures and had no negative influence on the sensory acceptability (appearance, colour, consistency, taste) of the products.…”
Section: Introductionmentioning
confidence: 99%
“…14 β-glucan here functions as a thickening agent due to its viscosity. 15,16 There are several additional benefits from β-glucan, such as inducing production of growth factors, cytokines and chemokines, and promoting cell migration and collagen synthesis. 17 Furthermore, the specific type of β-glucan used in this formulation that is derived from baker's yeast is known to have immune-modulatory function that is beneficial for wound healing as well.…”
Section: Discussionmentioning
confidence: 99%